Implementasi Perda Kab. Karo No. 01 Tahun 2024 Terhadap Pungutan Liar pada Objek Wisata Sidebuk-Debuk Perspektif Maqashid Syari’ah - Utami, Imiati Rohma; Br. Ginting, Elvira Dewi (Nagari Law Review, 2024)
Illegal levies (pungli) are a form of corruption that is still a serious problem in Indonesia, including in the tourism sector. Although Karo Regency Regional Regulation No. 01 of 2024 has been enacted as an effort to regulate local levies, extortion practices still occur at Sidebuk-Debuk tourist attraction, Karo Regency, which has a negative impact on tourist convenience and local revenue. This research aims to analyze the implementation of the local regulation, identify obstacles in its implementation, and evaluate the phenomenon of extortion using the Maqashid Shari'ah approach. This research uses a qualitative method with data collection through in-depth interviews with various resource persons. The results show that the lack of socialization, weak supervision, and the habit of extortion that has been cultivated are the main obstacles in the implementation of the local regulation. From the Maqashid Shari'ah perspective, extortion contradicts the principles of protecting religion (Hifdz al-Din), soul (Hifdz al-Nafs), intellect (Hifdz al-'Aql), offspring (Hifdz al-Nasl), and property (Hifdz al-Mal). This study recommends increased supervision, more effective socialization, and strict law enforcement to reduce extortion practices and improve the quality of tourism services.